Intestinal Parasitemia and HIV/AIDS Co-infections at Varying CD4+ T-cell Levels - Samuel CK Tay; Eric Nii Okai Aryee; Kingsley Badu (HIV/AIDS Research and Treatment-Open Journal, 2017)
Background: Intestinal parasites, especially coccidian parasites, cause gastrointestinal symptoms such as severe diarrhoea which increases morbidity and mortality rates in people living with Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS), particularly in Sub-Saharan Africa. We examined the prevalence of intestinal parasites in people living with AIDS at different CD4+ T-cell levels. Method: Case-control studies were conducted over a four month period including a total of 672 participants, between the ages of 8 and 72 years. HIV screening and confirmatory tests were done. We examined stool samples by wet mount, followed by formol-ether concentration and staining with Modified Field’s and Ziehl Neelsen techniques. We also carried out fluorescence activated cell sorting (FACS) analyses to obtain their CD4+ T-cell levels. Results: The prevalence of intestinal parasites were significantly higher (25.2%) among HIV seropositives than HIV seronegative individuals (13.3%), (p<0.001). Coccidian parasites: Cystoisospora belli (formerly Isospora belli), Cryptosporidium and the round worm Strongyloides stercoralis infections were found exclusively in HIV seropositives. Cryptosporidium infections were more frequently observed in the rural cohort (p=0.039). C. belli, Cryptosporidium, Giardia lamblia and Strongyloides stercoralis infections were significantly higher in diarrhoeic stools. Microsporidia and Cystoisospora belli were found mostly in individuals with CD4+ T-cell levels of ≤200 cells/µL. Participants with CD4+ T-cell count of ≤50 cells/µL were associated with diarrhoea. Conclusion: The prevalence of opportunistic coccidian parasites remains high in HIV-infected individuals with low CD4+ T-cell counts. Routine diagnosis is recommended to ensure comprehensive care for HIV patients.